Vibratory Surface Finishing of Additive Components Prepared from the Laser Powder Bed Fusion Process - Khan, Hamaid Mahmood; Koç, Ebubekir (CRC Press, 2023)
Traditionally seen as a promising technology for producing small, lowquality prototypes, 3D printing is widening its potential by becoming faster and more dependable. Instead of cutting a shape from a bigger block or casting a molten material in a mould, 3D printing entails adding items layer by layer, making the process more cost-effective and material-efficient.